Delivery of the selenoprotein thioredoxin reductase 1 to mammalian cells - Wright, David E.; Siddika, Tarana; Heinemann, Ilka U.; O’Donoghue, Patrick (Frontiers in Molecular Biosciences, 2022)
Over-expression of genetically encoded TrxR1 can be toxic to cells due to the formation of a truncated version of the enzyme. We developed a new mammalian cell-based model to investigate TrxR1 activity. Fusion of the HIV-derived cell penetrating peptide (TAT) enabled efficient uptake of purified TrxR1 containing 21 genetically encoded amino acids, including selenocysteine. The TAT peptide did not significantly alter the catalytic activity of TrxR1 in vitro. We monitored TrxR1-dependent redox activity in human cells using a TrxR1-specific red fluorescent live-cell reporter. Using programmed selenocysteine incorporation in Escherichia coli, our approach allowed efficient production of active recombinant human selenoprotein TrxR1 for delivery to the homologous context of the mammalian cell. The delivered TAT-TrxR1 showed robust activity in live cells and provided a novel platform to study TrxR1 biology in human cells.